Regards interdisciplinaires sur l'apport des technologies dans l'analyse du mouvement du service en tennis - Peter, J.-M.; Martin, C. (Movement & Sport Sciences - Science & Motricité, 2017)
An interdisciplinary approach is the art of working together, with people stemming from diverse scientific or technical disciplines. It allows a dialogue and an exchange of knowledge, between two or several disciplines, with a possible continuation in the training protocols. In this article, the project is to connect two researchers, on one hand from the social sciences, on the other hand one stemming from biomechanics, to review the use of the technologies in the analysis of the movement of the service and its efficient transmission from a historical perspective. To illustrate our purpose, we limit our analysis to only the service's movement.